Development of Probing-Prompting Learning Model Assisted by Mathematics Learning Module to Improve Students' Motivation and Mathematics Learning Outcomes - Siti Nur Halimah; Nurma Izzati; Sirojudin Wahid (Journal of General Education and Humanities, 2022)
This study has the following objectives: 1) To determine the development of the probing-prompting learning model assisted by the mathematics learning module to increase students' motivation and mathematics learning outcomes, 2) To test the effectiveness of the probing-prompting learning model assisted by the mathematics learning module to increase motivation and learning outcomes in mathematics student. This type of research is an RnD (Research and Development) model using the 4-D method that Thiagarajan and Sammel developed, namely the Define, Design, Develop, and Disseminate stages. This research was conducted at SMPN 01 Banjarharjo with a sample of 64 students. Collected data in this study using several instruments, including implementing learning plans, tests, motivation, and student response questionnaires. The results that have been obtained from the research are: 1) the Probing-Prompting learning model assisted by the Learning Module, after being validated and tested, it shows that it is convenient in increasing student motivation and learning outcomes, 2) The application of the Probing-Prompting learning model assisted by the Learning Module, can be said to be effective with an increase that occurred in students' motivation and mathematics learning outcomes.